THE USE OF AUTHENTIC VIDEO MATERIALS FOR THE DEVELOPMENT OF LANGUAGE SKILLS OF STUDENTS OF PHYLOLOGICAL UNIVERSITIES - Ibrokhimova Lobar Iskhokovna , Toshboyeva Munojat Erkinovna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
As you know, through language you can express any thought using different language means. Teaching a foreign language is an essential component of the curriculum in schools and universities. Different methods and means are used in teaching English. One of the most common means is the use of video materials. With the spread of the communicative approach, the concept of "authenticity" entered the methodology of teaching a foreign language in order to bring the learning process as close as possible to natural communication. Pedagogy has come a long and tortuous path in the study of ways and methods of effective teaching foreign languages, based on the achievements of technical progress, logic, semiotics and psychology. The video allows teacher to teach foreign language communication, taking into account various sociolinguistic factors presented with the help of visual information and in many respects determining the nature of the speech statements of the communicants, namely: their social status, the nature of relationships, spatio-temporal conditions of communication, etc. Thatiswhy a new milestone in the history of teaching has become the use of authentic audiovisual forms of teaching, combining visual and auditory perceptual components. The relevance of the topic choice is determined by changes in teaching priorities, which imply a greater use of audiovisual teaching methods. Despite the fact that it is still impossible to guarantee the absence of problems associated with their use (such as the lack of the required technical equipment, the inability of many teachers to work with modern equipment), the attractiveness of working with authentic video materials is obvious. Theyimmersestudentsin a natural language environment, contribute to the intensification of learning, stimulate the speech-thinking, cognitive, creative activity of students, and allow individualizing learning.